MODIFIKASI ALAT TANGKAP UDANG LAUT (Penaeus sp) MENGGUNAKAN BUBU BERBAHAN BAMBU - Ully Wulandari; Suharyanto Suharyanto; Deden Zainudin (Politeknik Kelautan dan Perikanan Dumai, 2021)
The research with the title Modification of Sea Shrimp Fishing Equipment (Penaeus sp) Using Bamboo Bubu and bubu nets (synthetic) was conducted for three months, starting from March-May 2020 at the Fishing Gear Laboratory of Karawang Marine and Fisheries Polytechnic. The purpose of this study is to make a modified bamboo bubu fishing tool and know the number of catches. The research was conducted by ekperimental method of bamboo bubu fishing equipment used to catch shrimp (Paneus sp). This research resulted in bubu units that have been modified using bamboo and bubu nets (synthetic). Both bubu were tested simultaneously. The trial was conducted by conducting an arrest operation in Cikumpay Lake, Purwakarta for 15 days. The test results showed the dominant catch obtained was macrobarachium placidulum shrimp which measured on average 5.8 cm with bamboo bubu and 4.5 cm with bubu net (synthetic). The average number of catches obtained by bamboo bubu is 41 prawns/day while for bubu nets (synthetic) 6 prawns/day.